Analysis of Work Motivation on Lecturers’ Work Productivity at The Faculty of Economics and Islamic Business UIN Raden Mas Said Surakarta - Rifky Aditya; Daneza Dhea Ananda Putri; Sekar Afifah Nur Fauziyah (Journal of Economic, Religious, and Entrepreneurship (JoERE), 2023)
In general, various factors influence work productivity, such as motivation, assessment, training, and development but in this article, researchers will only focus on the work motivation of lecturers. Work motivation has an important role in improving work productivity. Work motivation will be the driving force for lecturers to carry out tasks or obligations. This research method is qualitative research using case study techniques through interviews with sources. According to research, the trigger for the emergence of work motivation in lecturers are influenced by several factors, firstly is the desire for life (desire of life) which  related to the salary, compensation, and bonuses provided by the college or place of work; secondly, the desire for position and power (the desire for position and power), where this is related to promotion; and finally, the desire for recognition (the desire of recognition), which is recognized for lecturer contributions and lecturer performance, giving praise for the achievements achieved by lecturers. Motivation also has an impact on lecturers, such as improving lecturer performance, lecturer productivity, and lecturer job satisfaction, which leads to the success of higher education.